2016
DOI: 10.21082/jae.v23n1.2005.54-70
|View full text |Cite
|
Sign up to set email alerts
|

Family-Coping Strategies in Maintaining Welfare During The Economic Crisis In Indonesia: A case study in rural and urban areas in Bogor, West Java, Indonesia

Abstract: ABSTRAKLima tahun setelah krisis ekonomi yang akut melanda Indonesia (1997), proses pemulihan kehidupan berjalan sangat lambat. Masih dibutuhkan upaya untuk mengidentifikasi cara meningkatkan kesejahteraan keluarga. Tulisan ini merupakan bagian dari penelitian dengan judul yang sama, dengan tujuan (1) mengidentifikasi kesejahteraan keluarga di perkotaan dan pedesaan sebelum dan selama krisis ekonomi, (2) mengidentifikasi dampak krisis ekonomi terhadap penghasilan dan pengeluaran keluarga di daerah pedesaan dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
9
0
3
Order By: Relevance
“…Hasil ini sejalan dengan penelitian Kusumo (2009) yang menyatakan bahwa sebagian keluarga petani padi tidak terlalu merasakan kesulitan dalam hal memenuhi kebutuhan pangan, baik pada musim tanam maupun musim paceklik. Menurut Mardiharini (2005) strategi yang paling efektif dipilih keluarga dalam menyikapi dampak krisis adalah dengan mengurangi pengeluaran untuk makanan dan nonmakanan serta meningkatkan produktivitas usaha. Pada batas tertentu, pengeluaran pangan tidak bisa dikurangi lagi, baik jumlah maupun jenisnya.…”
Section: Pembahasanunclassified
“…Hasil ini sejalan dengan penelitian Kusumo (2009) yang menyatakan bahwa sebagian keluarga petani padi tidak terlalu merasakan kesulitan dalam hal memenuhi kebutuhan pangan, baik pada musim tanam maupun musim paceklik. Menurut Mardiharini (2005) strategi yang paling efektif dipilih keluarga dalam menyikapi dampak krisis adalah dengan mengurangi pengeluaran untuk makanan dan nonmakanan serta meningkatkan produktivitas usaha. Pada batas tertentu, pengeluaran pangan tidak bisa dikurangi lagi, baik jumlah maupun jenisnya.…”
Section: Pembahasanunclassified
“…Studies found significant association of food insecure households with borrowing money/food and selling valuable materials [26,27], which is similar to our findings. Norhasmah et al (2010), Mardiharini (2005) and Agbola (2008) identified that households during food insecurity, tended to borrow money from friends and relatives, sell or pawn own assets to get cash and purchase food on credit [15], [13], [28]. Borrowing money from friends or relative could be considered positive but selling or pawning to get money is very negative strategy; this strategy may lead to an immediate solution to decrease food insecurity level but it is not a sustainable approach.…”
Section: Discussionmentioning
confidence: 99%
“…Little research has looked at the impact of chronic food insecurity in countries experiencing the nutrition transition. During food insecurity, households adopt certain strategies or plan strategically to minimize its impact [12]- [13]. It is important to understand these strategies so as to identify what is being done at household or micro-level and how the communities cope up with the situations of food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Corbett (1988) reported households reducing number of meals per day as a coping mechanism Studies found significant association of food insecure households with borrowing money/ food and selling valuable materials (Shariff & Khor, 2008;Studdert et al, 2001). Mardiharini (2016) and Agbola (2008) identified that households during food insecurity, tended to borrow money from friends and relatives, sell or pawn own assets to get cash and…”
Section: Coping Strategies Adopted By Vegetables Farmersmentioning
confidence: 99%